Effect of Prebiotic on Microbiota, Intestinal Permeability, and Glycemic Control in Children With Type 1 Diabetes - Ho, Josephine; Nicolucci, Alissa C; Virtanen, Heidi; Schick, Alana; Meddings, Jon; Reimer, Raylene A; Huang, Carol (The journal of clinical endocrinology and metabolism, 2019)
Abstract Context Patients with type 1 diabetes (T1D) have lower microbiota diversity and distinct gut microbial profiles that have been linked to changes in intestinal permeability. Prebiotics are nondigestible carbohydrates that alter gut microbiota and could potentially improve glycemic control and reduce intestinal permeability and thereby insulin sensitivity. Objective To determine the effect of prebiotics on glycemic control, gut microbiota, and intestinal permeability in children with T1D. Design A randomized, placebo-controlled trial in children 8 to 17 years of age with T1D using placebo or prebiotic oligofructose-enriched inulin for 12 weeks. Baseline, 3-month, and 6-month assessments included HbA1c, C-peptide, gut microbiota, intestinal permeability, frequency of diabetic ketoacidosis (DKA), and severe hypoglycemia. Results Forty-three subjects were randomized and 38 completed the study. The groups were similar at baseline: prebiotic (N = 17), age 12.5 years (SD of 2.8), HbA1c 8.02% (SD of 0.82); placebo (N = 21), age 12.0 years (SD of 2.6), HbA1c 8.08% (SD of 0.91). No significant differences were found in the frequency of DKA or severe hypoglycemia. At 3-months, C-peptide was significantly higher (P = 0.029) in the group who received prebiotics, which was accompanied by a modest improvement in intestinal permeability (P = 0.076). There was a significant increase in the relative abundance of Bifidobacterium within the prebiotic group at 3 months that was no longer present after the 3-month washout. The placebo group had significantly higher relative abundance of Streptococcus, Roseburia inulinivorans, Terrisporobacter, and Faecalitalea compared with the prebiotic group at 3 months. Conclusion Prebiotics are a potentially novel, inexpensive, low-risk treatment addition for T1D that may improve glycemic control. Further larger-scale trials are needed. Children with type 1 diabetes were randomized to a placebo or prebiotic group. The prebiotic group showed significantly higher C-peptide and increased relative abundance of Bifidobacterium.